2019
DOI: 10.3389/fpsyg.2019.00775
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination and Personal Finances: Exploring the Roles of Planning and Financial Self-Efficacy

Abstract: Procrastination is related to unhealthy personal financial behaviors, such as postponing retirement savings, last minute shopping, and not paying bills on time. The present paper explores factors that could explain why procrastinators demonstrate more financial problems compared to non-procrastinators. Study 1 ( N = 675) focused on planning, as both procrastination and poor financial habits are negatively related to planning. Results confirmed that procrastination was a significant predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 56 publications
1
38
0
8
Order By: Relevance
“…This result could stem from the fact that individuals who score very high on the FSE scale are inherently very capable of handling financial distress and can deal with financial anxiety without any external motivators. Research has also shown that high FSE has a very strong relationship with positive financial behavior (Farrell et al, 2016;Lim et al, 2014;Danes and Haberman, 2007;Asebedo et al, 2019;Gamst-Klaussen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This result could stem from the fact that individuals who score very high on the FSE scale are inherently very capable of handling financial distress and can deal with financial anxiety without any external motivators. Research has also shown that high FSE has a very strong relationship with positive financial behavior (Farrell et al, 2016;Lim et al, 2014;Danes and Haberman, 2007;Asebedo et al, 2019;Gamst-Klaussen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Planning for financial wellness could also be negatively affected due the problem of information overload whereby individuals feel there is too much information, and this makes it more difficult to make retirement decisions. Some further concrete reasons why people don’t save enough for the future are that people don’t have enough money or income [ 22 ], have other goals, think they have more time, thought their job was a short gig so they don’t invest in a retirement plan, or don’t believe it is important and necessary [ 23 ] or even simple procrastination [ 24 ]. For millennials, key reasons include a focus on student debt, or employers don’t offer retirement plan, or a perception that they don’t have enough money and therefore consciously decide not to save [ 25 ].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Outrossim, Zhu, Bagchi e Hock (2019) explicam a lógica do comportamento e sua relação com o custo do atraso das tarefas, apontando que quanto mais distante o prazo, menor a percepção do custo e maior a probabilidade de procrastinar. Além disso, como a produtividade é vislumbrada como um valor (Gamst-Klaussen, Steel, & Svartdal, 2019), os indivíduos tendem a buscar um conforto psicológico ao iniciar a realização de tarefas não por ordem de prioridade, mas de acordo com seu grau de complexidade. Assim, iniciam por aquelas que requerem menor esforço (Rusou, Amar, & Ayal, 2020).…”
Section: Procrastinaçãounclassified